ANALISIS GAYA BELAJAR PESERTA DIDIK SEBAGAI DASAR PENYUSUNAN PROGAM BELAJAR KELAS VIII - Iskandar, Abdul Muis; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbsractLearning style is the way that selected learners tend to react and use stimulants-stimulant in absorbing and then organize and manipulate information on the learning process. For a teacher knows the style of learning each learner is the important thing because it can be in the set as reference in selecting the style of teaching that is appropriate. Common problems of the research is